In vitro Propagation of Mortiño (Vaccinium floribundum Kunth.) - Llivisaca, Susana; Cevallos, Juan Cevallos; Mendoza, Joffre; Piña, Fernando; Peralta, Esther; Timm, Eduardo Sanchez; Flores, José (Plant Tissue Culture and Biotechnology, 2020)
The disinfected axillary shoots of mortino - a wild plant species were cultured in MS with different concentrations (0.002, 0.05 and 0.1%) of methyl N-(1H-benzimidazol-2-yl) carbamate to develop an in vitro protocol for micropropagation through organogenesis. They were then placed in a concentration matrix (0.1, 1.0 and 10.0 μM) whose factorial design involved BAP and IAA in WPM. Results showed a 100% disinfection at 0.05% concentrations of carbendazim and the combination of IAA and BAP at 10 μM yielded a multiplication factor of 3.35, with rooting after seven weeks. This system showed efficient disinfection, multiplication and yielding an acceptable root system. Plant Tissue Cult. & Biotech. 30(2): 167-177, 2020 (December)